SISTEM AKUISIS DATA KOMPUTER PADA SENSOR ULTRASONIC RANGER UNTUK PENGUKURAN LEVEL MUKA AIR - Suryono, Suryono; Surarso, Bayu; Saputra, Ragil (BERKALA FISIKA, 2013)
This paper describes the method of ultrasound ranger development, data acquisition system and its characteristic than applied for automation water level distance measurement system using personal computer. This system is very important for recorded of water level data acquisition inlong time so data communication at measurement system.The system consist of ultrasonic distance sensor, microcontroller for time-of-flight counter and   serial interface,  and computer system fordata acquisition system. The microcontroller drive of sensor for generate of burst pulse. The 16-bitof counter of  microcontroller  was used for time-of-flight counter. Data was transmitted tocomputer twice at 8-bit of counter register. The microcontroller transmitted data at 9600 BPSusing UART protocols and slave-master for serial communication system. The communicationsystem was connected at voltage level communication RS232. The computer application of dataacquisition system was connected at COM port using Cport pellete in Borland Delphi. Thecollected data calibrated using standard.  The result of system characterization  have highmeasurement stability system at 99,61%, range of measurement distance at 10 cm to 280 cm,linear correlation with standard measurement at R = 0,9999, so it good for more application.Keywords : distance, pulse, counter, serial communication